Analysis of city size distribution in Ethiopia: Empirical evidence from 1984 to 2012 - Amha Ermias; Jan Bogaert; Fisseha Wogayehu (Journal of Urban Management, 2019)
Urbanisation in Ethiopia is increasing rapidly. This paper uses city-level data to investigate the evolution of Ethiopia's city size distribution from 1984 to 2012, using descriptive statistics and time-series Gini coefficient calculations. Over that period, the study found that overall city size distribution followed an apparent parallel growth pattern, with disparities among the country's regional states. This demonstrates that the parallel growth rule of city size distribution found in developed countries and most emerging economies applies in Ethiopia. Findings suggest that changes in the country's city size distribution from 1984 to 2007 resulted from changes in the political system and policy issues. The results enhance understanding of the evolution of Ethiopia's city size distribution and have important implications for policy debates.
Keywords: 710; City size distribution; Ethiopia; Gini coefficient; Urbanisation